Rancang Bangun Lampu Jalan Tenaga Surya Pada Jembatan Penghubung Desa Di Kabupaten Lebak Banten - Yoakim Simamora; Adri Senen; Tri Wahyu Oktaviana Putri; Dwi Anggaini (Sekolah Tinggi Teknik - PLN, 2020)
Road is a vital public facility that connects one region to another region. Hence, the existence of public street lighting is a key to supports people’s activities at night. But not all roads are equipped with public street lighting. For example, the village roads in Sukarame Village, Sajira sub-district, Lebak regency, Banten. This village is fully electrified but the supply for public street lighting is still limited. Therefore, it is neccesary to install public street lighting in the form of solar lamps as an effective alternative for street lighting and public facilities. Solar lamp is chosen because it doesn’t need power supply and the village’s geographical is very potential for utilizing solar lamps. Solar lamps installed in 3 strategic points, which are village road in front of local kindergarten, village road in front of public field, and mosque’s terrace. Besides solar lamp installation, this research also focused in economic analysis of this program. The analysis was done by comparing total cost needed for conventional public street lighting using bulbs that connect to grid with total cost needed for public street lighting using solar lamps. Despite solar lamp’s price is more expensive, for the long-term usage, public street lighting using solar lamps is more economically profitable compared to conventional public street lighting with the cost difference of Rp 636,582.80 per lamppost for 3 years usage period.